The Effect Of Administration Of Paitan (Tithonia Diversifolia) Liquid Extract On The Growth Of Tissue Cultural Products Of Barangan Banana (Musa Acuminata L.) Seedlings - Friza Elinda; Zhikry Fadhillah Miswar; Andre Sparta; Aulia Meyuliana; John Hendri (Department of Crop Science, Faculty of Agriculture, Andalas University, 2023)
Bananas (Musa spp.) are tropical plants that are very popular in Indonesia. Banana plants in the nursery require a planting medium that contains the nutrients the plants need. Tithonia is an annual weed that is suitable for use as a source of plant nutrients. This research aims to determine the effect of giving Tithonia liquid extract on the growth of Barangan banana seedlings resulting from tissue culture at the seedling stage and the best dose for using Tithonia liquid extract. This research was conducted at the Germplasm Nursery and Breeding Laboratory of the Tropical Fruit Plant Research Institute, Solok, West Sumatra, from September to December 2020. This research used the RAL method (Completely Randomized Design) with four treatments and six replications, in the form of 1) Without Tithonia extract, 2) Giving 1 ml of Tithonia extract, 3) Giving 2 ml of Tithonia extract, and 4) Giving 3 ml of Tithonia extract. The parameters observed were plant height, number of leaves, leaf length, leaf width, and stem diameter. Data was tested statistically. If calculated F > F table then it is tested further using the Duncan Multiple Range Test (DNMRT) with a level of 5%. The results of the research showed that giving Tithonia liquid extract had an effect on the growth of Barangan banana seedlings resulting from tissue culture. Significantly different results were obtained for the leaf width increase parameter. On the other hand, the results were not significantly different for other parameters such as plant height, number of leaves, leaf length and stem diameter. Giving 1 ml of Tithonia liquid extract was the best dose in this study.